Efeitos no remodelamento ventricular esquerdo por dietas com diferentes teores de sódio após o infarto do miocárdio em ratos normotensos e hipertensos - Forechi, Ludimila (2015)
Diet of sodium restriction is a standard approach after an acute myocardial infarction (MI). Very low levels of sodium intake, however, can activate the renin-angiotensinaldosterone system and change the ventricular remodeling. We have hypothesized wether the use of a high or low-sodium diet would interfere post-infarction ventricular remodeling and facilitate the development of heart failure. Male normotensive (Wistar) and hypertensive (SHR) rats with 8 weeks were used. MI was produced by surgical ligature of the left coronary artery and control animals underwent a sham surgery (SHAM). After surgery, the animals were assigned to receive, for 60 days, the standard diet (0.3% NaCl), or diets with high (0.6% NaCl) or low (0.03% NaCl) sodium content. The systolic blood pressure (tail plethysmography), food intake (metabolic cages) and body weight were measured in three different moments during the treatment period. After this period, the rats were anesthetized to evaluate the left ventricular performance during cardiac. The animals were submitted to a intravenous infusion of KCl to evaluate the left ventricular stiffness by in situ pressure-volume curve. Left ventricular slices stained with hematoxylin-eosin were used to determine myocyte hypertrophy, and stained with picrosirius to evaluate fibrosis. The results showed that post-MI mortality was highir in SHR unrelated to the diet (21.43% in Wistar and 55% in SHR; p=0,012). In Wistar, only the high-salt diet increased the mortality (44.22%). Low-salt diet did not prevent fibrosis increase after MI (Wistar: 5.0±0.4% and 5.2±0.5%, and SHR: 7.3±0.4% and 6.3±0.4% under standard and lowsodium diet respectively). The High-salt diet increased the collagen in SHAM rats (Wistar: 3.3±0.4% and 4.7±0.4%, and SHR: 3.8±0.3% and 6.2±0.2% under standard and high sodium diet, respectively) with no additional increase after MI. The ventricular stiffness was also increased after MI in animals SHR under high-salt diet (4.6±0.3 mmHg/mL in SHAM and 7.7±0.4 mmHg/mL in MI rats under high-sodium diet). The moderate increase of sodium in the diet increased the blood pressure of the normotensive rats (124±1.4 mmHg and 145±5,1 mmHg under standard and high sodium diet, respectively) and worsened the hypertension of the SHR rats (189±4.0 mmHg/mL and 202±0.1 mmHg). The low-salt diet prevented the increase of the left ventricular systolic pressure in SHR (134±3.8 mmHg in standard diet and 123±3.1 mmHg in high sodium diet). However, the left ventricular function did not worsen by different diets after MI. Our results show that post-MI ventricular remodeling was not affected by the immediate introduction of low sodium diet after MI> Therefore, sodium resctriction seems to be a safe therapeutic intervention to prevent fluid retention. However, diets with high sodium content seems inadequate in such cases because they increase mortality and accelerate the post-infarction ventricular remodeling.